Local Approximation Properties of Modified Baskakov Operators - Ozarslan, M. Ali; Duman, Oktay; Mahmudov, Nazim I. (Birkhauser Verlag Ag, 2011)
In this paper, we introduce a general modification of the classical Baskakov operators which do not need to preserve the test function x (2). Then, we study an approximation theorem, a Voronovskaya theorem, and various local approximation results for our modified Baskakov operators.
Keywords: Baskakov operators; the modulus of continuity; the second modulus of smoothness; Peetre's K-functional; the Voronovskaya theorem